Development of a point-of-care (POC) diagnostic system - Lee, Shinhan. (2012)
This report covers the development work of the final year project “The development of a point-of-care Diagnostic system” over the course of 2 semesters. The POC diagnostic system is to be used for the diagnostic of cancerous diseases and infectious diseases using the immunoassays technique, The detection method is based on the innovative Localized Surface Plamonic Resonance (LSPR) with nanosize patterned metal layer on the glass substrate, called the LSPR chip. The LSPR chip is integrated in the microfluidic cartridge with multiple microchannels. The testing cartridge is made in polymer substrate and consists of the inlet chamber, microchannels for fluidic flow control and the reaction chamber s to hold the LSPR chips, as well as the waste chamber to contain the spent biosample and reagents.